Top–down activation of spatiotopic sensory codes in perceptual and working memory search - Kuo, B-C; Nobre, AC; Scerif, G; Astle, DE (MIT Press, 2016)
A critical requirement of an efficient cognitive system is the selection and prioritization of relevant information. This occurs when selecting specific items from our sensory inputs, which then receive preferential status at subsequent levels of processing. Many everyday tasks also require us to select internal representations, such as a relevant item from memory. We show that both of these types of search are underpinned by the spatiotopic activation of sensory codes, using both fMRI and MEG data. When individuals searched for perceived and remembered targets, the MEG data highlighted a sensor level electrophysiological effect that reflects the contralateral organization of the visual system—namely, the N2pc. The fMRI data were used to identify a network of frontoparietal areas common to both types of search, as well as the early visual areas activated by the search display. We then combined fMRI and MEG data to explore the temporal dynamics of functional connections between the frontoparietal network and the early visual areas. Searching for a target item resulted in significantly enhanced phase–phase coupling between the frontoparietal network and the visual areas contralateral to the perceived or remembered location of that target. This enhancement of spatially specific phase–phase coupling occurred before the N2pc effect and was significantly associated with it on a trial-by-trial basis. The combination of these two imaging modalities suggests that perceptual and working memory search are underpinned by the synchronization of a frontoparietal network and the relevant sensory cortices.